Rhodamine B doped silicon dioxide / xylan carbon dot composite material as well as preparation method and application thereof
By loading rhodamine B and xylan carbon dots on silica nanospheres, a detection probe based on proportional fluorescence was constructed, which solved the problems of long detection time, expensive equipment and complex operation in the prior art, and achieved high sensitivity and high specificity detection of Vibrio parahaemolyticus.
Patent Information
- Application Number
- CN202411647189.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing Vibrio parahaemolytic detection technology has problems such as long detection time, expensive equipment, and complex operation, making it difficult to achieve fast, simple, sensitive and specific detection.
By loading rhodamine B and xylan carbon dots on silica nanospheres and coupling with DNA double helix short chains through covalent bonding, a detection probe based on proportional fluorescence was constructed. The red fluorescence intensity emitted by RhB@SiO2 was used as the internal standard to conduct quantitative detection based on the ratio of the blue fluorescence intensity of BCD to R.
It realizes high sensitivity and specificity detection of Vibrio parahaemolyticus, reduces detection errors, improves detection reliability and cost-effectiveness, and is suitable for the detection of seawater and clam samples.
Smart Images

Figure CN119510755A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of organic / inorganic nano hybrid composite materials, and in particular to a rhodamine B-doped silica / xylan carbon dot composite material and a preparation method thereof. Background Art
[0002] Vibrio parahaemolyticus is a common pathogen in seafood, contaminating fish, shrimp, shellfish, plankton and other near-shore aquatic organisms. Vibrio parahaemolyticus food poisoning caused by eating raw or undercooked seafood products can cause diseases such as acute gastroenteritis, wound infection, and sepsis. Monitoring the presence of Vibrio parahaemolyticus in seafood is a crucial food safety task. Among the existing Vibrio parahaemolyticus detection technologies, the traditional culture method is still the standard method for qualitative and quantitative Vibrio parahaemolyticus. However, the culture method requires multiple steps such as bacterial enrichment, separation, and culture identification, which is extremely time-consuming. In addition, the rapid detection method based on PCR technology requires a complex detection system, expensive instruments, and relies on laboratories with dedicated infrastructure and well-trained experimental personnel. Therefore, it is urgent to develop a detection method with fast response, simple operation, sensitive detection, and good specificity for daily monitoring, large-scale screening, and emergency treatment of food safety.
[0003] The detection method based on the fluorescence principle is convenient to measure, simple to operate, highly sensitive, highly reliable, cost-effective, and has the adaptability to on-site detection. Carbon dots (CDs) are well-dispersed spherical particles with a particle size of less than 10nm. As an important fluorescent nanomaterial, they have attracted much attention due to their interesting properties, such as high stability, water solubility, biocompatibility, antibacterial properties, non-toxicity, excellent electron transfer efficiency, abundant edge defects and adjustable photoluminescence properties. Among them, lignocellulose has gradually become a popular carbon source for low-cost preparation of CDs because of its wide source, low cost, and green environmental protection. Lignocellulose is the most abundant biological resource in nature, composed of cellulose, hemicellulose and lignin. Hemicellulose is a type of heteropolysaccharide that connects cellulose and lignin, accounting for 20-35% of lignocellulose. Xylan is the main type of hemicellulose and is often used as a model of hemicellulose. It has the advantages of wide source, low cost, renewable, biodegradable, good biocompatibility, good solubility, high accessibility, and high hydrothermal carbon yield. By using xylan as a carbon source and undergoing a hydrothermal preparation process, a series of blue fluorescent materials with abundant carboxyl groups can be constructed, and fluorescent probe functional materials can be further constructed, thus providing new ideas for the high-value utilization of biomass.
[0004] However, at present, most fluorescence detection platforms for bacterial detection use monochromatic fluorescence as output signals. Such detection platforms are susceptible to the influence of the environment, buffer composition, other interfering compounds, instrument changes, changes in excitation light sources, and even experimental operations, resulting in false positive or false negative results, and reliability cannot be guaranteed. In order to overcome this inherent disadvantage, the number of output signals of the fluorescence detection platform is increased from a single to two, and the self-calibration function is realized by measuring the dual fluorescence ratio signal, minimizing interference and improving analytical dependence. Therefore, Rhodamine B is introduced as an internal standard fluorescence signal. Rhodamine B can emit an orange fluorescence with a wavelength of 575nm when excited, and its wavelength and the blue fluorescence emitted by carbon dots have a good wavelength interval in terms of excitation wavelength, and have spectral decoupling characteristics. However, Rhodamine B has the problem of easy quenching in the detection system, and at the same time, the step of adding Rhodamine B is also easy to increase the system error in the detection process. In order to protect Rhodamine B from external influences and system errors of the detection system, silica with the advantages of optical transparency, adjustable size and morphology, easy surface functionalization, good biocompatibility, and high chemical and thermodynamic stability was selected as an optical protective agent for Rhodamine B. Silica has great application value in the fields of biological imaging, chemical sensing, optoelectronic device manufacturing, anti-counterfeiting technology, etc. The use of silica shells to wrap fluorescent materials such as fluorescent dyes and carbon dots can not only increase the doping amount of fluorescent materials and amplify the fluorescent signal, but also protect the fluorescent materials from quenching due to the influence of the external environment and increase the stability of the fluorescent materials. Multifunctional silica composite materials can be constructed by assembling, coating or integrating one or more different luminescent materials inside and on the surface of silica nanoparticles in different ways.
[0005] Therefore, the study used silica as a carrier, integrated fluorescent dyes and fluorescent carbon dots inside and on the surface of silica, and then realized the construction of a dual fluorescence ratio signal probe to prepare a rhodamine B-doped silica / xylan carbon dots-aptamer composite material. Summary of the invention
[0006] The object of the present invention is to provide a method for detecting Vibrio parahaemolyticus ratio fluorescence based on silica-loaded rhodamine B and xylan carbon dots. In the method, rhodamine B and tetraethyl silicate are uniformly mixed in ethanol to form rhodamine B-doped silica nanospheres (RhB@SiO2). Blue fluorescent carbon dots (BCD) are covalently linked to RhB@SiO2 to obtain SiO2 (RhB@SiO2 / BCD) with dual-color fluorescence emission. A short DNA double helix chain is formed by a complementary chain grafted to the surface of BCD, and a single-chain aptamer (Apt.D) with a quencher connected to one end is coupled to the carbon dots, and the single-chain aptamer specifically targets Vibrio parahaemolyticus. When Vibrio parahaemolyticus is present in the test sample, Apt.D detaches from the surface of BCD and binds to the recognition site on the surface of Vibrio parahaemolyticus, so that the fluorescence of BCD is restored. In the above manner, a detection probe based on ratiometric fluorescence was established, the red fluorescence intensity (R) emitted by RhB@SiO2 was used as the internal standard, and the quantitative detection of Vibrio parahaemolyticus was performed according to the ratio of the blue fluorescence intensity (B) of BCD to R. The object of the present invention is also to provide a Rhodamine B-doped silica / xylan carbon dot composite material prepared by the above method.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] A method for detecting Vibrio parahaemolyticus ratio fluorescence based on silica-loaded rhodamine B and xylan carbon dots, firstly, rhodamine B and tetraethyl silicate are uniformly mixed in ethanol to form rhodamine B-doped silica nanospheres RhB@SiO2, then xylan carbon dots are covalently linked to the surface of RhB@SiO2, and finally a single-stranded aptamer (Apt.D) with a quencher at one end is coupled to BCD through a surface-grafted complementary chain to form a DNA double helix short chain, specifically comprising the following steps:
[0009] (1) Preparation of RhB@SiO2:
[0010] Prepare an ethanol solution of rhodamine B, add tetraethyl silicate, stir to make the mixture evenly dispersed, then add ammonia water and continue the reaction; after the reaction is completed, add it to the evenly dispersed tetraethyl silicate ethanol solution, stir, then add ammonia water and deionized water in sequence, continue stirring to react, add tetraethyl silicate and ammonia water again, and continue the reaction; after the reaction is completed, centrifuge to obtain a precipitate, and wash it with ethanol several times to obtain rhodamine B-doped silica RhB@SiO2;
[0011] (2) Surface amination of RhB@SiO2:
[0012] RhB@SiO2 was resuspended in an ethanol solution, and 3-aminopropyltriethoxysilane was added while stirring to continue the reaction. After the reaction was completed, the precipitate was collected by centrifugation to obtain RhB@SiO2-NH2;
[0013] (3) Preparation of BCD:
[0014] The xylan is prepared in a NaOH / urea aqueous solution, stirred evenly, and reacted under pressurized heating conditions; after the reaction is completed, the precipitate is removed by centrifugation, and dialyzed to obtain a xylan carbon dot solution;
[0015] (4) Preparation of RhB@SiO2 / BCD:
[0016] 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide were added to the xylan carbon dot solution in proportion, and after activation, they were mixed evenly with RhB@SiO2-NH2 and stirred for reaction. After the reaction, the precipitate was obtained by centrifugation and washed several times to obtain the RhB@SiO2 / BCD composite material.
[0017] (5) Preparation of RhB@SiO2 / BCD-Apt.D:
[0018] 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are added in proportion to the redispersed liquid of the RhB@SiO2 / BCD composite material, and after activation, a complementary DNA short chain for Apt.D is added to react; after the reaction, the precipitate is obtained by centrifugation, washed several times, and redispersed in water, and Apt.D modified with a quencher is added, and the reaction is gently stirred; after the reaction, the precipitate is centrifuged and washed several times to obtain RhB@SiO2 / BCD-Apt.D.
[0019] Furthermore, in step (1), in the ethanol solution of rhodamine B, the concentration of rhodamine B is 2-6 mg / mL, the concentration of tetraethyl silicate is 0.5-2.5% (volume ratio), and the concentration of ammonia water is 15-25% (wt.).
[0020] Furthermore, in step (1), the reaction temperature is room temperature, about 20 to 30°C.
[0021] Furthermore, in step (1), the temperature of the first stage reaction is 20-30° C., and the time is 30-90 hours; the concentration of the tetraethyl silicate ethanol solution is 1-5%, and the time of the second stage reaction is 3-12 hours; and the reaction time after the last addition of tetraethyl silicate and ammonia water is 6-24 hours.
[0022] Furthermore, in step (2), the volume ratio of the RhB@SiO2-NH2 dispersion and ethanol is 5-10:30-35, and the concentration of 3-aminopropyltriethoxysilane is 1-5% (v. / v.).
[0023] Furthermore, in step (2), the reaction time is 12 to 48 hours.
[0024] Furthermore, in step (3), the weight average molecular weight of the xylan is 4.5×10 4 ~5.5×10 4 g / mol, and by weight percentage, the sugar groups are: 85.00-90.00% xylose, 7.50-12.00% arabinose, 0.50-1.00% glucose, 0.20-0.70% galactose, and 1.05-2.95% glucuronic acid.
[0025] Furthermore, in step (3), in the NaOH / urea aqueous solution of xylan, the concentration of xylan is 20-50 g / L, the concentration of NaOH is 5-10% (wt.), and the concentration of urea is 10-15% (wt.).
[0026] Furthermore, in step (3), the hydrothermal temperature is 200-260°C.
[0027] Furthermore, in step (3), the reaction time is 12 to 24 hours.
[0028] Furthermore, in step (3), the concentration of the xylan solution is 0.1-0.2 mg / ml.
[0029] Furthermore, in step (3), the weight average molecular weight of the xylan is 4.5×10 4 ~5.5×10 4 g / mol, and by weight percentage, the sugar groups are: 85.00-90.00% xylose, 7.50-12.00% arabinose, 0.50-1.00% glucose, 0.20-0.70% galactose, and 1.05-2.95% glucuronic acid.
[0030] Furthermore, in step (4), the concentration of the xylan carbon dots is 0.1 to 0.2 mg / mL.
[0031] Furthermore, in step (4), the concentration of the 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride solution is 30 to 50 mg / mL.
[0032] Furthermore, in step (4), the concentration of the N-hydroxysuccinimide solution is 20 to 40 mg / mL.
[0033] Furthermore, in step (4), the activation time is 15 to 60 minutes, preferably 15 to 30 minutes, and the reaction time is 2 to 4 hours.
[0034] Furthermore, in step (5), the concentration of the rhodamine B-doped silica / xylan carbon dot composite redispersion liquid is 10 to 20 mg / mL; the concentration of the 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 30 to 50 mg / mL; the concentration of the N-hydroxysuccinimide is 20 to 40 mg / mL; the concentration of the DNA short-chain primer for fixation is 25 to 100 μmol / L, and the volume is 100 μL; the activation time is 15 to 60 min ; The binding reaction time of the DNA short-chain primer and the rhodamine B-doped silica / xylan carbon dots is 1 to 3 hours; the binding reaction of Apt.D and the DNA short-chain primer has a reaction time of 2 to 4 hours as described below; the concentration of the Apt.D is 25 to 100 μmol / L, and the reaction time after adding Apt.D is 2 to 4 hours; the concentration of the Vibrio parahaemolyticus aptamer primer modified with a quencher is 100 μM, and the volume is 100 μL; the reaction time of the gentle stirring process is 1 to 3 hours.
[0035] A Vibrio parahaemolyticus ratio fluorescence detection method based on silica-loaded rhodamine B and xylan carbon dots prepared by any of the preparation methods described above.
[0036] The application of the rhodamine B-doped silica / xylan carbon dot composite material as a fluorescent sensor; specifically: when Vibrio parahaemolyticus exists in the test sample, Apt.D detaches from the BCD surface and binds to the recognition site on the surface of Vibrio parahaemolyticus, so that the fluorescence of BCD is restored. Through the above method, a detection probe based on ratio fluorescence is established, and the red fluorescence intensity R emitted by RhB@SiO2 is used as an internal standard. Vibrio parahaemolyticus is quantitatively detected according to the ratio of the blue fluorescence intensity B of BCD to R.
[0037] Compared with the prior art, the present invention has the following advantages:
[0038] (1) The present invention prepares a ratio fluorescence detection method for Vibrio parahaemolyticus based on silica-loaded rhodamine B and xylan carbon dots, adopts a ratio fluorescence model with built-in standards and a response model of fluorescence recovery, avoids the systematic error influence of a complex detection environment on a single fluorescence signal, and the fluorescent sensor constructed by the prepared nanocomposite material realizes specific recognition of Vibrio parahaemolyticus based on DNA base matching and competition, has the advantages of high sensitivity, high specificity, low cost, greenness, good biocompatibility, etc., has important research and application value in synthesizing bacterial detection probes based on ratio fluorescence, and can realize the detection of Vibrio parahaemolyticus in seawater and clam samples, and has broad application prospects in foodborne bacteria detection and monitoring.
[0039] (2) The present invention introduces rhodamine B and adds optically inert silica as a protection for rhodamine B, thereby reducing the system errors caused by changes in the external environment and experimental operations, and generating a stable and reliable internal standard fluorescence signal. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1a It is the infrared absorption spectra of SiO2, RhB@SiO2 and RhB@SiO2-NH2 in Example 1;
[0041] Figure 1b The infrared absorption spectra of BCD, RhB@SiO2 / BCD, and RhB@SiO2 / BCD-Apt.D in Example 1;
[0042] Figure 2a The fluorescence spectra of SiO2, RhB@SiO2, RhB@SiO2 / BCD, and RhB@SiO2 / BCD-Apt.D in Example 1;
[0043] Figure 2b The zeta potential diagrams of SiO2, RhB@SiO2, RhB@SiO2 / BCD, and RhB@SiO2 / BCD-Apt.D in Example 1;
[0044] Figure 3 This is the sensitivity performance diagram of the RhB@SiO2 / BCD-Apt.D composite material in Example 1 in the detection of Vibrio parahaemolyticus;
[0045] Figure 4a Thermogravimetric diagrams of RhB@SiO2 and pure rhodamine B in Example 1;
[0046] Figure 4b This is the photobleaching trace of RhB@SiO2 and pure Rhodamine B in Example 1. DETAILED DESCRIPTION
[0047] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings, but the implementation manner and protection scope of the present invention are not limited thereto.
[0048] The xylan used in the specific embodiment of the present invention is extracted from bagasse, and the weight average molecular weight of xylan is 4.5×10 4 ~5.5×10 4 g / mol, and by weight percentage, the sugar groups are: 85.00-90.00% xylose, 7.50-12.00% arabinose, 0.50-1.00% glucose, 0.20-0.70% galactose, and 1.05-2.95% glucuronic acid.
[0049] Example 1
[0050] The preparation of the Rhodamine B-doped silica / xylan carbon dot composite material and its fluorescence sensor specifically comprises the following steps:
[0051] (1) Disperse 4.79 mg of rhodamine B and 1 mL of tetraethyl silicate in 10 mL of anhydrous ethanol, stir magnetically for 15 min, then slowly add 800 μL of ammonia water and continue stirring for 80 min to obtain a RhB@SiO2 precursor solution; at the same time, prepare another tetraethyl silicate dispersion solution: disperse 1 mL of tetraethyl silicate in 30 mL of anhydrous ethanol and stir for 30 min to obtain a tetraethyl silicate dispersion solution; slowly add the RhB@SiO2 precursor solution to the tetraethyl silicate dispersion solution, stir magnetically for 30 min, then add 1 mL of ammonia water and 3 mL of water, and react for 6 hours; then, add 3 mL of tetraethyl silicate and 4 mL of ammonia water, continue magnetic stirring for 18 hours to obtain RhB@SiO2.
[0052] (2) RhB@SiO2 was dispersed in 40 mL of ethanol solution, 1 mL of 3-aminopropyltriethoxysilane was added, and the mixture was stirred and reacted at room temperature (about 24°C) for 24 hours.
[0053] The infrared spectra of silica nanospheres, RhB@SiO2 and RhB@SiO2-NH2 are shown in Figure 1. Figure 1a It can be seen that the three silica nanospheres are all at 1400 cm -1 , 1095cm -1 , 955cm -1 , 800cm -1 The Si-O stretching vibration peak, the Si-O-Si bond antisymmetric stretching vibration peak, and the Si-OH bending vibration peak are shown at 1232 cm -1 There is an obvious CN stretching vibration peak enhancement at 3460cm -1 The broad peaks of symmetric and asymmetric stretching vibrations of amino groups (-NH2) at the 400 nm region confirmed that the surface of the silica nanospheres had been successfully modified by amino group.
[0054] (3) Preparation of BCD
[0055] A NaOH / urea aqueous solution of xylan was prepared, wherein the concentration of NaOH was 12% (w. / w.) and the concentration of urea was 8% (w. / w.), and after being stirred evenly, the mixture was reacted at 260° C. for 24 hours. After the reaction was completed, the precipitate was removed by centrifugation, and dialyzed to obtain BCD.
[0056] (4) 38.34 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 23.02 mg of N-hydroxysuccinimide were added to 5 mL of BCD solution and activated for 30 min under magnetic stirring. After activation, 5 mL of aminated rhodamine B-doped silica nanospheres were added and stirred at room temperature for 2 hours to obtain RhB@SiO2 / BCD carbon dots.
[0057] (5) Then, 40 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 40 mg of N-hydroxysuccinimide were added to 3 mL of RhB@SiO2 / BCD dispersion, and the mixture was activated by magnetic stirring in a water bath at 37°C for 30 min. Subsequently, 100 μL of 50 μmol / L short DNA chain (fssDNA) for immobilization (5'-ATT TTT AGA CGAAT TTTTT-NH2-3', purchased from Beijing Qingke Biotechnology Co., Ltd.) was added, and the reaction was continued by stirring for 12 hours. Finally, 100 μL of 50 μmol / L Apt.D (5'-ATTCG TCT AAA AAT GGG CAA AGA AAC AGT GAC TCG TTG AGA TACT-Dabcyl-3', purchased from Beijing Qingke Biotechnology Co., Ltd.) was added, and the reaction was continued at 37°C for 2 hours to obtain RhB@SiO2 / BCD-Apt.D composite material.
[0058] Figure 1b The infrared absorption spectra of BCD, RhB@SiO2 / BCD, and RhB@SiO2 / BCD-Apt.D. Figure 1b It can be seen from the infrared spectrum curve of BCD that 1630cm -1 The strong signal characteristic absorption peak at 1232cm is attributed to the C=O bond of the abundant carboxyl groups on BCD. In the infrared spectrum curves of RhB@SiO2 / BCD and RhB@SiO2 / BCD-Apt.D, there are Si-O stretching and bending vibration peaks and Si-O-Si bond antisymmetric stretching vibration peaks belonging to silica. In addition, the RhB@SiO2 / BCD composite material is located at 1232cm -1 The signal of the CN bond at 1600cm-1 decreased after connecting with BCD, and the content of CN bonds belonging to primary amine groups decreased, indicating that the amino groups on the surface of the silica spheres were amidated during the connection with BCD. Since the quencher used in the RhB@SiO2 / BCD-Apt.D composite material is Dabcyl, which contains a CN bond and a carbonyl C=O bond connected to the benzene ring in its molecular structure, the quencher at 1600cm-1 decreased after connecting with BCD, and the content of CN bonds belonging to primary amine groups decreased, indicating that the quencher at 1600cm-1 decreased during the connection with BCD. -1 The CN bond characteristic peak at 1630cm -1 The carbonyl characteristic peak signals at the positions are all enhanced.
[0059] Figure 2a The fluorescence spectra of Rhodamine B, xylan carbon dots, RhB@SiO2, RhB@SiO2 / BCD, and RhB@SiO2 / BCD-Apt.D. As can be seen from the figure, doping Rhodamine B into silica nanospheres only slightly reduces the fluorescence intensity of Rhodamine B at 575nm, but the protection of silica can prevent Rhodamine B from quenching caused by changes in the external environment. The RhB@SiO2 / BCD composite material can simultaneously emit blue fluorescence belonging to BCD and orange fluorescence belonging to RhB@SiO2 under ultraviolet excitation. After coupling with Apt.D, the blue fluorescence emission intensity belonging to BCD is significantly reduced, providing a fluorescence recovery interval for constructing a recovery-type fluorescent probe.
[0060] Figure 2b This is the Zeta potential diagram of Rhodamine B, xylan carbon dots, RhB@SiO2, RhB@SiO2-NH2, RhB@SiO2 / BCD, and RhB@SiO2 / BCD-Apt.D. The Zeta potentials of Rhodamine B and RhB@SiO2 are -2.69mV and -14.4mV, respectively. After surface amino modification, the Zeta potential of RhB@SiO2 rises to +30.3mV, indicating that the surface amino modification is successful. Since the surface of xylan carbon dots is negatively charged at -14.3mV, the composite of xylan carbon dots reduces the surface charge of RhB@SiO2 / BCD material to -34.7mV. After further composite with Apt.D, the surface Zeta potential of RhB@SiO2 / BCD-Apt.D material increases to -16.7mV.
[0061] Figure 3 The sensitivity of the RhB@SiO2 / BCD-Apt.D composite fluorescent probe in the detection of Vibrio parahaemolyticus was investigated. As the concentration of Vibrio parahaemolyticus increased exponentially, the RhB@SiO2 / BCD-Apt.D composite fluorescent probe showed that the blue fluorescence from BCD gradually recovered, while the orange fluorescence intensity from RhB@SiO2 remained roughly unchanged. The ratio of blue fluorescence intensity to red fluorescence intensity was calculated, and the ratio showed a good linear relationship with the bacterial concentration of Vibrio parahaemolyticus Y (ratio of blue to red fluorescence) = 2.37X (Log10 of bacterial concentration) + 0.031 (R 2 =0.9827), and achieved a detection limit of 1.14 CFU / mL (S / N=3) and 8-8×10 5 Detection range of CFU / mL.
[0062] Figure 4aThermogravimetry was used to investigate the effect of the optically inert protective layer of silica on Rhodamine B. Rhodamine B began to lose weight at 250°C and completely lost weight at 550°C, with a total weight loss of about 70%. After Rhodamine B was protected by doping it inside silica nanospheres, RhB@SiO2 showed a normal weight loss trend with increasing temperature, but the total weight loss was only about 10%. Rhodamine B is embedded in the mesh spaces of silica and is bound by nano-silica, making it less likely to lose weight. At 40°C to 150°C, the weight loss mainly comes from the evaporation of free water in the silica pores and pure rhodamine.
[0063] Figure 4b The photobleaching traces of Rhodamine B and RhB@SiO2 under full-band xenon lamp irradiation conditions are shown. Under xenon lamp irradiation, Rhodamine B undergoes photobleaching, and the fluorescence intensity of the characteristic fluorescence peak at 575nm gradually decreases from 758 to 441.9, a decrease of 41.7%. However, Rhodamine B doped in nano-silica spheres is embedded in the pores of the silica mesh and protected by silica. The fluorescence intensity of the characteristic fluorescence peak at 575nm decreases from 789.5 to 605.2, a decrease of only 23.34%. This shows that silica plays an important role in protecting the Rhodamine B internal standard from photobleaching.
[0064] Example 2
[0065] The preparation of the Rhodamine B-doped silica / xylan carbon dot composite material and its fluorescence sensor specifically comprises the following steps:
[0066] (1) Disperse 10 mg of rhodamine B and 1.5 mL of tetraethyl silicate in 10 mL of anhydrous ethanol, stir magnetically for 15 min, then slowly add 1 mL of ammonia water, and continue stirring for 60 min to obtain a rhodamine B-doped silica nanosphere precursor solution; at the same time, prepare another tetraethyl silicate dispersion solution: disperse 3 mL of tetraethyl silicate in 30 mL of anhydrous ethanol, stir for 30 min to obtain a tetraethyl silicate dispersion solution; slowly add the rhodamine B-doped silica nanosphere precursor solution to the tetraethyl silicate dispersion solution, stir magnetically for 30 min, then add 2 mL of ammonia water and 5 mL of water, and react for 12 hours; then, add 3 mL of tetraethyl silicate and 4 mL of ammonia water, continue magnetic stirring for 24 hours, and obtain rhodamine B-doped silica nanospheres.
[0067] (2) Rhodamine B-doped silica nanospheres were dispersed in 30 mL of ethanol solution, 0.5 mL of 3-aminopropyltriethoxysilane was added, and the mixture was stirred and reacted at room temperature (about 24° C.) for 24 hours.
[0068] (3) Preparation of Xylan Carbon Dots
[0069] A NaOH / urea aqueous solution of xylan was prepared, wherein the concentration of NaOH was 8% (w. / w.), and the concentration of urea was 8% (w. / w.), and after being stirred evenly, the mixture was reacted at 200° C. for 24 hours. After the reaction was completed, the precipitate was removed by centrifugation, and dialyzed to obtain xylan carbon dots.
[0070] (4) 38.34 mg 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 23.02 mg N-hydroxysuccinimide were added to 2.5 mL of xylan carbon dots solution and activated for 30 min under magnetic stirring. After activation, 5 mL aminated rhodamine B-doped silica nanospheres were added and stirred at room temperature for 4 hours to obtain rhodamine B-doped silica / xylan carbon dots.
[0071] (5) Then, 30 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 30 mg of N-hydroxysuccinimide were added to 3 mL of the dispersion of rhodamine B doped silica / xylan carbon dots, and the mixture was activated by magnetic stirring in a 37°C water bath for 30 min. Subsequently, 100 μL of 50 μmol / L of the DNA short chain (fssDNA) for immobilization was added, and the reaction was continued by stirring for 12 hours. Finally, 100 μL of 50 μmol / L of the Vibrio parahaemolyticus aptamer modified with the quencher Dabcyl was added, and the reaction was continued at 37°C for 4 hours to obtain a rhodamine B doped silica / xylan carbon dots / Vibrio parahaemolyticus aptamer composite material.
[0072] Example 3
[0073] The preparation of the Rhodamine B-doped silica / xylan carbon dot composite material and its fluorescence sensor specifically comprises the following steps:
[0074] (1) Disperse 2.39 mg of rhodamine B and 1 mL of tetraethyl silicate in 10 mL of anhydrous ethanol, stir magnetically for 15 min, then slowly add 400 μL of ammonia water, and continue stirring for 60 min to obtain a rhodamine B-doped silica nanosphere precursor solution; at the same time, prepare another tetraethyl silicate dispersion solution: disperse 1 mL of tetraethyl silicate in 30 mL of anhydrous ethanol, stir for 30 min to obtain a tetraethyl silicate dispersion solution; slowly add the rhodamine B-doped silica nanosphere precursor solution to the tetraethyl silicate dispersion solution, stir magnetically for 30 min, then add 0.5 mL of ammonia water and 1 mL of water, and react for 12 hours; then, add 1.5 mL of tetraethyl silicate and 1 mL of ammonia water, continue magnetic stirring for 24 hours, and obtain rhodamine B-doped silica nanospheres.
[0075] (2) Rhodamine B-doped silica nanospheres were dispersed in 20 mL of ethanol solution, 1 mL of 3-aminopropyltriethoxysilane was added, and the mixture was stirred and reacted at room temperature (about 24° C.) for 24 hours.
[0076] (3) Preparation of Xylan Carbon Dots
[0077] A NaOH / urea aqueous solution of xylan was prepared, wherein the concentration of NaOH was 10% (w. / w.) and the concentration of urea was 8% (w. / w.), and after being stirred evenly, the mixture was reacted at 240° C. for 24 hours. After the reaction was completed, the precipitate was removed by centrifugation, and dialyzed to obtain xylan carbon dots.
[0078] (4) 38.34 mg 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 23.02 mg N-hydroxysuccinimide were added to 1 mL of the xylan carbon dots solution and activated for 30 min under magnetic stirring. After activation, 2.5 mL aminated rhodamine B-doped silica nanospheres were added and stirred at room temperature for 2 hours to obtain rhodamine B-doped silica / xylan carbon dots.
[0079] (5) Then, 40 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 40 mg of N-hydroxysuccinimide were added to 3 mL of the dispersion of rhodamine B doped silica / xylan carbon dots, and the mixture was activated by magnetic stirring for 30 min in a 37°C water bath. Subsequently, 100 μL of 10 μmol / L of the immobilized DNA short chain (fssDNA) was added, and the reaction was continued with stirring for 12 hours. Finally, 100 μL of 10 μmol / L of the Vibrio parahaemolyticus aptamer modified with the quencher Dabcyl was added, and the reaction was continued at 37°C for 2 hours to obtain a rhodamine B doped silica / xylan carbon dots / Vibrio parahaemolyticus aptamer composite material.
[0080] Example 4
[0081] The preparation of the Rhodamine B-doped silica / xylan carbon dot composite material and its fluorescence sensor specifically comprises the following steps:
[0082] (1) Disperse 40.7 mg of rhodamine B and 1 mL of tetraethyl silicate in 10 mL of anhydrous ethanol, stir magnetically for 15 min, then slowly add 1.6 mL of aqueous ammonia, and continue stirring for 80 min to obtain a rhodamine B-doped silica nanosphere precursor solution; at the same time, prepare another tetraethyl silicate dispersion solution: disperse 1 mL of tetraethyl silicate in 30 mL of anhydrous ethanol, stir for 30 min to obtain a tetraethyl silicate dispersion solution; slowly add the rhodamine B-doped silica nanosphere precursor solution to the tetraethyl silicate dispersion solution, stir magnetically for 30 min, then add 1 mL of aqueous ammonia and 3 mL of water, and react for 6 hours; then, add 3 mL of tetraethyl silicate and 4 mL of aqueous ammonia, continue magnetic stirring for 18 hours, and obtain rhodamine B-doped silica nanospheres.
[0083] (2) Rhodamine B-doped silica nanospheres were dispersed in 40 mL of ethanol solution, 2 mL of 3-aminopropyltriethoxysilane was added, and the mixture was stirred and reacted at room temperature (about 24° C.) for 24 hours.
[0084] (3) Preparation of Xylan Carbon Dots
[0085] A NaOH / urea aqueous solution of xylan was prepared, wherein the concentration of NaOH was 15% (w. / w.) and the concentration of urea was 10% (w. / w.), and after being stirred evenly, the mixture was reacted at 260° C. for 24 hours. After the reaction was completed, the precipitate was removed by centrifugation, and dialyzed to obtain xylan carbon dots.
[0086] (4) 383.4 mg 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 230.2 mg N-hydroxysuccinimide were added to 2.5 mL of xylan carbon dot solution and activated for 30 min under magnetic stirring. After activation, 5 mL aminated rhodamine B-doped silica nanospheres were added and stirred at room temperature for 4 hours to obtain rhodamine B-doped silica / xylan carbon dots.
[0087] (5) Then, 40 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 40 mg of N-hydroxysuccinimide were added to 3 mL of the dispersion of rhodamine B doped silica / xylan carbon dots, and the mixture was activated by magnetic stirring for 30 min in a 37°C water bath. Subsequently, 100 μL of 50 μmol / L of a short DNA chain (fssDNA) for immobilization was added, and the reaction was continued with stirring for 12 hours. Finally, 100 μL of 50 μmol / L of a Vibrio parahaemolyticus aptamer modified with a quencher Dabcyl was added, and the reaction was continued at 37°C for 4 hours to obtain a rhodamine B doped silica / xylan carbon dots / Vibrio parahaemolyticus aptamer composite material.
[0088] Example 5
[0089] The preparation of the Rhodamine B-doped silica / xylan carbon dot composite material and its fluorescence sensor specifically comprises the following steps:
[0090] (1) Disperse 10 mg of rhodamine B and 2 mL of tetraethyl silicate in 10 mL of anhydrous ethanol, stir magnetically for 15 min, then slowly add 1 mL of ammonia water, and continue stirring for 80 min to obtain a rhodamine B-doped silica nanosphere precursor solution; at the same time, prepare another tetraethyl silicate dispersion solution: disperse 3 mL of tetraethyl silicate in 30 mL of anhydrous ethanol, stir for 30 min, and obtain a tetraethyl silicate dispersion solution; slowly add the rhodamine B-doped silica nanosphere precursor solution to the tetraethyl silicate dispersion solution, stir magnetically for 30 min, then add 1 mL of ammonia water and 3 mL of water, and react for 12 hours; then, add 3 mL of tetraethyl silicate and 4 mL of ammonia water, and continue magnetic stirring for 24 hours to obtain rhodamine B-doped silica nanospheres.
[0091] (2) Rhodamine B-doped silica nanospheres were dispersed in 40 mL of ethanol solution, 4 mL of 3-aminopropyltriethoxysilane was added, and the mixture was stirred and reacted at room temperature (about 24° C.) for 24 hours.
[0092] (3) Preparation of Xylan Carbon Dots
[0093] A NaOH / urea aqueous solution of xylan was prepared, wherein the concentration of NaOH was 10% (w. / w.) and the concentration of urea was 12% (w. / w.), and after being stirred evenly, the mixture was reacted at 260° C. for 24 hours. After the reaction was completed, the precipitate was removed by centrifugation, and dialyzed to obtain xylan carbon dots.
[0094] (4) 38.34 mg 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 23.02 mg N-hydroxysuccinimide were added to 0.5 mL of xylan carbon dots solution and activated for 30 min under magnetic stirring. After activation, 5 mL aminated rhodamine B-doped silica nanospheres were added and stirred at room temperature for 3.5 hours to obtain rhodamine B-doped silica / xylan carbon dots.
[0095] (5) Then, 40 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 40 mg of N-hydroxysuccinimide were added to 3 mL of the dispersion of rhodamine B doped silica / xylan carbon dots, and the mixture was activated by magnetic stirring for 30 min in a 37°C water bath. Subsequently, 50 μL of 10 μmol / L of the immobilized DNA short chain (fssDNA) was added, and the reaction was continued with stirring for 4 hours. Finally, 50 μL of 10 μmol / L of the Vibrio parahaemolyticus aptamer modified with the quencher Dabcyl was added, and the reaction was continued at 37°C for 2 hours to obtain a rhodamine B doped silica / xylan carbon dots / Vibrio parahaemolyticus aptamer composite material.
[0096] The above embodiments are only preferred implementation modes of the present invention and are only used to explain the present invention rather than to limit the present invention. Any changes, substitutions, combinations, simplifications, modifications, etc. made by those skilled in the art without departing from the spirit and principles of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a rhodamine B-doped silica / xylan carbon dot composite material, characterized in that: The steps include: (1) Preparation of RhB@SiO2: Prepare an ethanol solution of rhodamine B, add tetraethyl silicate, stir to make the mixture evenly dispersed, then add ammonia water and continue the reaction; after the reaction is completed, add it to the evenly dispersed tetraethyl silicate ethanol solution, stir, then add ammonia water and deionized water in sequence, continue stirring to react, add tetraethyl silicate and ammonia water again, and continue the reaction; after the reaction is completed, centrifuge to obtain a precipitate, and wash it with ethanol several times to obtain rhodamine B-doped silica RhB@SiO2; (2) Surface amination of RhB@SiO2: RhB@SiO2 was resuspended in an ethanol solution, and 3-aminopropyltriethoxysilane was added while stirring to continue the reaction. After the reaction was completed, the precipitate was collected by centrifugation to obtain RhB@SiO2-NH 2; (3) Preparation of BCD: The xylan is prepared in a NaOH / urea aqueous solution, stirred evenly, and reacted under pressurized heating conditions; after the reaction is completed, the precipitate is removed by centrifugation, and dialyzed to obtain a xylan carbon dot solution; (4) Preparation of RhB@SiO2 / BCD: 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide were added to the xylan carbon dot solution in proportion, and after activation, they were mixed evenly with RhB@SiO2-NH2 and stirred for reaction. After the reaction, the precipitate was obtained by centrifugation and washed several times to obtain the RhB@SiO2 / BCD composite material. (5) Preparation of RhB@SiO2 / BCD-Apt.D: 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are added in proportion to the redispersed liquid of the RhB@SiO2 / BCD composite material, and after activation, a complementary DNA short chain for Apt.D is added to react; after the reaction, the precipitate is obtained by centrifugation, washed several times, and redispersed in water, and Apt.D modified with a quencher is added, and the reaction is gently stirred; after the reaction, the precipitate is centrifuged and washed several times to obtain RhB@SiO2 / BCD-Apt.D.
2. The method for preparing a rhodamine B-doped silica / xylan carbon dot composite material according to claim 1, characterized in that: In step (1), in the ethanol solution of rhodamine B, the concentration of rhodamine B is 2-6 mg / mL, the volume percentage concentration of tetraethyl silicate is 0.5-2.5%, and the mass percentage concentration of ammonia water is 15-25wt%; the temperature of the first stage reaction is 20-30° C., and the reaction time is 30-90 h; the concentration of the ethanol solution of tetraethyl silicate is 1-5%, and the reaction time of the second stage is 3-12 h; and the reaction time after the last addition of tetraethyl silicate and ammonia water is 6-24 h.
3. The method for preparing a Rhodamine B-doped silica / xylan carbon dot composite material according to claim 1, characterized in that: In step (2), the volume percentage concentration of 3-aminopropyltriethoxysilane is 1 to 5%; and the reaction time is 12 to 48 hours.
4. The method for preparing a rhodamine B-doped silica / xylan carbon dot composite material according to claim 1, characterized in that: In step (3), the weight average molecular weight of the xylan is 4.5×10 4 ~5.5×10 4 g / mol, and by weight percentage, the sugar groups are: 85.00-90.00% xylose, 7.50-12.00% arabinose, 0.50-1.00% glucose, 0.20-0.70% galactose, and 1.05-2.95% glucuronic acid.
5. The method for preparing a Rhodamine B-doped silica / xylan carbon dot composite material according to claim 1, characterized in that: In step (3), the concentration of xylan is 20-50 g / L, the mass percentage concentration of NaOH is 5-10% (wt.), the mass percentage concentration of urea is 10-15% (wt.), the hydrothermal temperature is 200-260° C., and the reaction time is 12-24 h.
6. The method for preparing a rhodamine B-doped silica / xylan carbon dot composite material according to claim 1, characterized in that: In step (4), the concentration of the xylan carbon dot solution is 0.1-0.2 mg / mL; the concentration of the 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 30-50 mg / mL; the concentration of the N-hydroxysuccinimide is 20-40 mg / mL; the activation time is 15-60 min; and the reaction time is 2-4 h.
7. The method for preparing a Rhodamine B-doped silica / xylan carbon dot composite material according to claim 1, characterized in that: In step (5), the concentration of the rhodamine B-doped silica / xylan carbon dot composite redispersion liquid is 10 to 20 mg / mL; the concentration of the 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 30 to 50 mg / mL; the concentration of the N-hydroxysuccinimide is 20 to 40 mg / mL; the concentration of the fixed DNA short-chain primer is 25 to 100 μmol / L, and the volume is 100 μL; the activation time is 15 to 60 min; D The binding reaction time of NA short-chain primer and rhodamine B-doped silica / xylan carbon dots is 1 to 3 hours; the binding reaction of Apt.D and DNA short-chain primer has a reaction time of 2 to 4 hours as described below; the concentration of Apt.D is 25 to 100 μmol / L, and the reaction time after adding Apt.D is 2 to 4 hours; the concentration of Vibrio parahaemolyticus aptamer primer modified with a quencher is 100 μM, and the volume is 100 μL; the reaction time of the gentle stirring process is 1 to 3 hours.
8. A Rhodamine B-doped silica / xylan carbon dot composite material prepared by the preparation method according to any one of claims 1 to 5.
9. Use of the Rhodamine B doped silica / xylan carbon dots composite material as claimed in claim 8 as a fluorescence sensor.
10. The use according to claim 9, characterized in that: When Vibrio parahaemolyticus is present in the test sample, Apt.D detaches from the BCD surface and binds to the recognition site on the surface of Vibrio parahaemolyticus, causing the fluorescence to recover. Through the above method, a detection probe based on ratio fluorescence was established. The red fluorescence intensity R emitted by RhB@SiO2 was used as the internal standard, and the quantitative detection of Vibrio parahaemolyticus was performed according to the ratio of the blue fluorescence intensity B of BCD to R.
Citation Information
Patent Citations
Method for detecting tetracycline and clenbuterol by carbon dot-rhodamine B bifluorescence system proportional fluorescence probe
CN110441280A
Hemostatic, antibacterial and healing-promoting hydrogel with real-time monitoring function and preparation method
CN114920956A
Xylan-based carbon dots with multicolor fluorescence and preparation method thereof
CN118406488A
Synthesis of CDs / GO-PBA nano-composite probe and detection method of salmonella
CN118406489A
Method for the modification of polymeric carbohydrate materials
WO2003033813A1